On Timescales and Reversibility of the Ocean's Response to Enhanced Greenland Ice Sheet Melting in Comprehensive Climate Models - Martin, Torge; Biastoch, Arne; Lohmann, Gerrit; Mikolajewicz, Uwe; Wang, Xuezhu; Biastoch, Arne; 1 GEOMAR Helmholtz‐Zentrum Für Ozeanforschung Kiel Kiel Germany; Lohmann, Gerrit; 3 Alfred‐Wegener‐Institut Helmholtz‐Zentrum Für Polar‐ und Meeresforschung Bremerhaven Germany; Mikolajewicz, Uwe; 4 Max‐Planck‐Instiut Für Meteorologie Hamburg Germany; Wang, Xuezhu; 3 Alfred‐Wegener‐Institut Helmholtz‐Zentrum Für Polar‐ und Meeresforschung Bremerhaven Germany (Geophysical Research Letters, 2022)
Warming of the North Atlantic region in climate history often was associated with massive melting of the Greenland Ice Sheet. To identify the meltwater's impacts and isolate these from internal variability and other global warming factors, we run single‐forcing simulations including small ensembles using three complex climate models differing only in their ocean components. In 200‐year‐long preindustrial climate simulations, we identify robust consequences of abruptly increasing Greenland runoff by 0.05 Sv: sea level rise of 44 ± 10 cm, subpolar North Atlantic surface cooling of 0.7°C, and a moderate AMOC decline of 1.1–2.0 Sv. The latter two emerge in under three decades—and reverse on the same timescale after the perturbation ends in year 100. The ocean translates the step‐change perturbation into a multidecadal‐to‐centennial signature in the deep overturning circulation. In all simulations, internal variability creates notable uncertainty in estimating trends, time of emergence, and duration of the response. Plain Language Summary: Enhanced melting of Greenland's glaciers is considered to be a major player in past rapid climate transitions and anticipated to soon impact ocean circulation under current global warming. Global warming triggers complex processes and feedbacks, of which greater amounts of meltwater slowing the large‐scale ocean circulation is only one. To better understand the sensitivity of the real but also the model ocean to just this meltwater, we run idealized experiments with up‐to‐date climate models, which use the same atmosphere and land but different ocean components. We find that sea level rise, cooling of the North Atlantic region, and slowing of the ocean circulation are responses common to all models while regional magnitudes of these responses differ considerably. Once we stop adding freshwater, all three models show that surface temperature and ocean circulation recover as quickly (or slowly) as they changed at the beginning of the experiment. Sea level rise is a lasting impact ...